Analisis Implementasi Perda No 1 Tahun 2024 Tentang Kebijakan Parkir Berlangganan Berbasis Barcode Di Kota Medan - Caroline Pakpahan, Lisa; Alona Br Bangun, Jacklyn; Wahyuni, Devi Sri; Fiona Purba, Desriani Ronay; Panggabean, Naulita; Ivanna, Julia (Universitas Jabal Ghafur, 2025)
The implementation of Regional Regulation No. 1 Year 2024 on Barcode-Based Subscription Parking Policy in Medan City aims to improve transparency and efficiency in the parking system. This research uses a descriptive qualitative approach by applying interview, observation, and document analysis techniques to identify the effectiveness and challenges in implementing this policy. The results indicate that although this policy aims to reduce illegal levies and increase local revenue, the implementation still faces various obstacles, such as mismatches in field implementation, lack of supervision, and indecisiveness in rule enforcement. Therefore, strategic measures are needed, such as increased supervision, wider socialization, and increased transparency in fund management, so that this policy can run effectively and provide real benefits to the community. Translated with DeepL.com (free version)Keywords : parking subscription, public policy, policy implementation, Medan City